Well-designed environmental regulation and firm performance: Swedish evidence on the Porter hypothesis and the effect of regulatory time strategies. Issue 2 (28th January 2019) - Weiss, Jan; Stephan, Andreas; Anisimova, Tatiana
Abstract : Using recent data on a cross-section of Swedish chemical and pulp and paper firms, this paper provides novel empirical insights into the Porter hypothesis. Well-designed environmental regulation can stimulate firms' innovative capabilities, while at the same time generating innovation offsets that may both offset net compliance costs and yield a competitive edge over those firms that are not affected by such regulations. In doing so, we also test the alleged effectiveness of regulatory time strategies in stimulating innovation activities of regulated firms. We find evidence for the effectiveness of such well-designed regulations: announced rather than existing regulation induces innovation and some innovation offsets. Our results imply that empirical tests of the Porter hypothesis that do not account for its dynamic nature, and that do not measure well-designed regulations, might provide misleading conclusions as to its validity.